Post-Retention Results of Spring-Loaded Posterior Bite-Block Therapy - Akkaya Sevil; Haydar Seda (Sciendo, 1996)
In this study, ten patients who were treated with spring-loaded posterior bite blocks (SLPBB), were evaluated over a period of two years in order to test the effects of the appliance and the incidence of relapse. Successful treatment with SLPBB was achieved in skeletal and dental open bite cases. However, the use of acrylic bite blocks for retention during the post-treatment growth period, did not prevent relapse.